Size selectivity of diamond and square mesh codends for largehead hairtail Trichiurus lepturus Linnaeus, 1758 - Rajeswari, Govathoti; Raghu Prakash, R.; Sreedhar, U; Swamy Kumar, M. (Indian Journal of Fisheries, 2013)
Trawl codend mesh selectivity with respect to largehead hairtail Trichiurus lepturus was studied along Andhra Pradesh coast. Covered codend method was used to obtain the selectivity data. The L25, L50 and L75 values for 40 mm square mesh codend were 30.75, 36.2 and 41.65 mm respectively with the selection range, selection factor and selection ratio being 10.9 and 9.05 and 0.30 respectively. The L25, L50 andL75 values for 40 mm diamond mesh codend were 25.96, 33.4 and 40.95 mm, the selection range, selection factor and selection ratio being 14.9, 8.35 and 0.44 respectively The retention mean length in square mesh was found to be greater than diamond mesh. The square mesh was also found to be more efficient in eliminating juveniles than conventional diamond mesh codend .